2003
DOI: 10.1007/s11908-003-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular complications in patients with HIV infection

Abstract: As advances in early diagnosis and aggressive therapy, as well as better supportive care, become available to a larger number of patients with HIV infection, survival is being prolonged, and more patients are experiencing cardiac abnormalities. The most common cardiac manifestations of HIV disease are dilated cardiomyopathy, myocarditis, pericardial effusion, endocarditis, pulmonary hypertension, HIV-associated malignant neoplasms, and drug-related cardiotoxicity. The introduction of highly active antiretrovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Pericardial effusion in HIV patients may be marker of end stage HIV infection because it is associated with low CD4 count. Table 4 [29] and Lipshultz et al [30] who have shown that cardiac manifestations occur late in the course of the disease. Previous studies have shown that HIV related cardiac manifestations are often seen in a state of severe immunosuppression with low CD4 Count (CD4 < 200/microL).…”
Section: Discussionmentioning
confidence: 94%
“…Pericardial effusion in HIV patients may be marker of end stage HIV infection because it is associated with low CD4 count. Table 4 [29] and Lipshultz et al [30] who have shown that cardiac manifestations occur late in the course of the disease. Previous studies have shown that HIV related cardiac manifestations are often seen in a state of severe immunosuppression with low CD4 Count (CD4 < 200/microL).…”
Section: Discussionmentioning
confidence: 94%
“…[1][2][3][4][5][6][7][8][9] Myocarditis is one of the most frequently recognized findings in HIV-infected individuals, with incidence rates as high as 52% reported. 6,[10][11][12][13] While the connection between HIV-associated myocarditis and clinical cardiac disease is still unclear given that the majority of cases are subclinical, there is considerable evidence to suggest the possibility of a contributory role.…”
Section: Introductionmentioning
confidence: 99%
“…25 Drug-related cardiotoxicities may also play a role in some cases. 1,26,27 Simian immunodeficiency viruses (SIV) are lentiviruses that are genetically closely related to HIV and represent the original sources from which both HIV-1 and HIV-2 derived. 28,29 SIV infection of Asian macaque species produces a fatal immunodeficiency syndrome with properties of disease progression very similar to those seen in humans with HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…The use of immunosuppressive regimens in these patients is controversial and no convincing benefits have been reported other than with intravenous immunoglobulin [Lipshultz et al, 1995], whose efficacy may reflect inhibition of cardiac auto antibodies by competition with Fc receptors or dampened effects of cytokines and cellular growth factors. The introduction of highly active antiretroviral therapy (HAART) regimens has substantially modified the course of HIV disease by lengthening survival and improving quality of life of HIV-infected patients [Zareba & Lipshultz 2003]. There is also good evidence that HAART significantly reduces the incidence of cardiovascular manifestations of HIV infection.…”
Section: Treatmentmentioning
confidence: 99%